The Effect of A Process Approach Using Report Writing Frame on Students’ Writing Achievement - Khoiriyatul Hariro (IJET (Indonesian Journal of English Teaching), 2017)
This study is aimed at investigating the effect of process approach using Report Writing Frame on students’ writing achievement. The design of this study was quasi-experimental design. The subjects of this study were the third-semester students of Academic Writing class of English Education Department of Brawijaya University of Malang. The result of t-test showed that the students who were taught using Report Writing Frame have better writing achievement than those who were taught without using Report Writing Frame. Besides, from the five categories or aspects which were scored; organization, content, grammar, vocabulary, and mechanic, it indicated that the students who were taught using Report Writing Frame had more significant improvement in term organization, content, and vocabulary.